Gastrointestinal Tract As Entry Route for Hantavirus Infection - Witkowski, Peter T.; Perley, Casey C.; Brocato, Rebecca L.; Hooper, Jay W.; Jürgensen, Christian; Schulzke, Jörg-Dieter; Krüger, Detlev H.; Bücker, Roland (Frontiers in Microbiology, 2017)
Background: Hantaviruses are zoonotic agents that cause hemorrhagic fevers and are thought to be transmitted to humans by exposure to aerosolized excreta of infected rodents. Puumala virus (PUUV) is the predominant endemic hantavirus in Europe. A large proportion of PUUV-infected patients suffer from gastrointestinal symptoms of unclear origin. In this study we demonstrate that PUUV infection can occur via the alimentary tract. Methods: We investigated susceptibility of the human small intestinal epithelium for PUUV infection and analyzed the resistance of virions to gastric juice. As model for intestinal virus translocation we performed infection experiments with human intestinal Caco-2 monolayers. In animal experiments we infected Syrian hamsters with PUUV via the intragastric route and tested seroconversion and protective immunity against subsequent Andes virus challenge. Results: PUUV retained infectivity in gastric juice at pH >3. The virus invaded Caco-2 monolayers in association with endosomal antigen EEA1, followed by virus replication and loss of epithelial barrier function with basolateral virus occurrence. Cellular disturbance and depletion of the tight junction protein ZO-1 appeared after prolonged infection, leading to paracellular leakage (leak flux diarrhea). Moreover, animal experiments led to dose-dependent seroconversion and protection against lethal Andes virus challenge. Conclusions: We provide evidence that hantavirus can infect the organism via the alimentary tract and suggest a novel aspect of hantavirus infection and pathogenesis. Significance: Hantaviruses are zoonotic pathogens causing severe hemorrhagic fevers worldwide. They are transmitted to humans by small mammals. To date, these viruses were thought to infect exclusively through the airborne route by inhalation of aerosols from infectious animal droppings or by rodent bites. In our work we could show that the alimentary tract is an alternative path of infection for hantaviruses, meaning a new association of virus and disease. These findings have impact on current textbook knowledge and bring many implications for hantavirus epidemiology and outbreak prevention measures.